MTMS-based aerogel structure deposition on polypropylene fibrous filter – Surface layer effect and distribution control for improvement of oil aerosol separation properties - Nowak, Bartosz; Bonora, Marta; Zuzga, Maria; Werner, Łukasz; Jackiewicz-Zagórska, Anna; Gac, Jakub M. (Journal of environmental chemical engineering, 2022)
Polypropylene non-woven material with fibres surface modified with methyltrimetoxysilane(MTMS)-based aerogel structure exhibits increased affinity to oil and highly developed collector area, which translates to enhanced oil mist filtration performance, crucial in automotive, commercial and home appliances. This article indicates the filtration improvement ability's dependence on the aerogel structure's deposition and morphology, as previous work raised some critical questions related to surface vs volume deposition's contribution to filtration properties. Modified and native materials were studied on a filtration test bench and via a systematic wettability investigation. The amount of aerogel structure deposit is correlated to the MTMS concentration, and its distribution relay on condensation kinetics, controlled by the catalyst addition rate during the sol-gel process. Though beneficial for separation efficiency improvement, the aerogel structure deposition in filter volume is accompanied by a surface foil layer formation that needs to be removed as it causes up to 200 Pa airflow resistance. The controlled aerogel structure deposition method gave satisfactory results, increasing separation efficiency for most penetrating droplets four times and increasing filter Quality Factor. Modified material is competitive in terms of separation efficiency and airflow resistance with those obtained in the other related works on the subject, giving a post-production method for oil aerosol filter enhancement. [Display omitted] •Method gives control on post-production improvement of filter properties.•Meso-macropore combination assures high separation efficiency and low pressure drop.•Aerogel deposition in filter volume is preferable to enhance separation properties.•Aerogel surface layer has a low impact on filtration efficiency and pressure drop.•Surface foil layer should be removed as it dramatically increases airflow resistance.